Handball - Cardinale, M. (Routledge handbook of strength and conditioning: Sport-specific programming for high performance, 2018)
Developing physical abilities in handball players requires a holistic approach. Research studies indicate that a training approach focused mostly on enhancing aerobic capacity to improve handball performance is possibly wrong. It is instead evident that knowledge of players` demands and technical and tactical requirements within a team should be the due diligence every strength and conditioning coach performs before individualising training. Strength and conditioning activities are of fundamental importance for handball players. An effective training programme has the potential not only to improve performance but also to reduce significantly the risk of injuries. It is important to note that there are very few longitudinal studies on handball players and more needs to be done in order to understand the most effective training prescriptions for elite handball players involved in national and international competi- tions during very long seasons. Despite the limited information available, it is clear that strength training programmes can produce beneficial effects when performed during the sporting season, and appropriate loading patterns and variety of exercise prescription is needed due to the specific needs of the sport and the specific requirements of playing positions. Practitioners should always assess the athletes in order to identify strengths and weaknesses and monitor the effectiveness of the training prescriptions using dynamometry and assessing vertical jumping abilities and throwing speed when possible. Some of the methods indicated in this book chapter have been very useful to assess progression not only over the course of the season, but also over the years in players of international calibre. However, it should be reminded that improvements in the gym (e.g. personal bests in 1RM or in CMJ) are only significant if they have a direct translation on handball specific elements (e.g. throwing speed, jumping ability and/or reduction in injury rates) and can improve the effectiveness and the decision making of a player or a team.